Layered oxide sodium-ion battery positive electrode material as well as preparation method and application thereof
By introducing heavy elements into the positive electrode material of sodium ion battery and building the O3-P2 composite phase structure, the problem of poor structural stability of the material is solved, and the electrochemical performance and cyclic stability are significantly improved.
Patent Information
- Application Number
- CN202510008344.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-04
AI Technical Summary
The existing positive electrode materials of sodium ion batteries have problems such as poor structural stability, low capacity and short cycle life, which limits the practical application of sodium ion batteries.
By introducing some heavy elements such as Mo, La, Ce, and W into the O-type layered oxide positive electrode material, the O3-P2 composite phase structure is constructed to stabilize the crystal structure and inhibit structural transformation.
The electrochemical performance of the material has been significantly improved, capacity and cycle stability have been improved, the discharge specific capacity has been increased by 9-15%, and the specific capacity holding capacity after 200 weeks of circulation has been improved by 24-30%.
Smart Images

Figure CN119764423A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of batteries, and specifically relates to a layered oxide sodium ion battery positive electrode material and a preparation method and application thereof. Background Art
[0002] In today's context of energy shortage and increasing environmental awareness, the development of efficient, environmentally friendly and safe energy storage and conversion technologies has become an important global issue. However, due to the continuous rise in lithium prices and the increased use of high-cost transition metal element nickel, the comprehensive cost of lithium-ion batteries continues to increase, and their application in the energy field has certain limitations. Therefore, it is particularly urgent to develop and seek low-cost and high-performance secondary ion batteries.
[0003] As a low-cost, high-performance energy storage device, sodium-ion batteries have broad application prospects in the fields of power grids, electric vehicles, etc. However, the current sodium-ion battery cathode materials on the market, such as Prussian blue compounds, polyanion structures, layered oxide materials, etc., have some problems, such as poor structural stability, low capacity, short cycle life, etc., which limit the practical application of sodium-ion batteries.
[0004] Among the existing layered oxide cathode materials for sodium-ion batteries, O3-type transition metal oxides are the most common. Compared with P-type oxides, they have higher capacity and energy density and are the most widely used cathode materials for sodium-ion batteries, such as O3-type oxides containing manganese, iron, nickel and copper. However, the electrochemical performance of these materials still needs to be improved. For example, the irreversible structural transformation during the sodium insertion and extraction process, the migration of iron atoms with JT effect from the transition metal layer to the sodium layer, and the poor air stability all lead to the poor structural stability and poor cycle performance of the O3 structure.
[0005] Therefore, there is an urgent need to provide a new sodium ion battery positive electrode material to solve the above technical problems. Summary of the invention
[0006] In view of the problems existing in the existing positive electrode materials for sodium ion batteries, the present invention proposes a new design and preparation method for layered oxide positive electrode materials, and further develops a layered oxide positive electrode material with excellent electrochemical properties and stability.
[0007] Specifically, the common O-type layered oxide positive electrode materials currently developed generally have low capacity, are prone to complex phase transitions during the charge and discharge process, are structurally unstable during the electrochemical reaction, and have poor cycles. The inventors of the present invention have found through research that the essence of solving these problems lies in adjusting the components to stabilize the structure and the phase transition behavior of the stable crystal structure during the charge and discharge process, thereby improving the electrochemical performance of the material and enhancing the capacity and cycle stability. The present invention innovatively proposes to introduce some heavy elements into the O-type layered oxide positive electrode material from the perspective of having a strong bond with oxygen, and utilizes these heavy elements such as Mo, La, Ce, W, etc. to have a strong and stable bond with oxygen in the lattice, so as to form a "locking effect" on the crystal structure during the charge and discharge process, thereby ensuring the stability of the crystal structure of the positive electrode material, inhibiting the destructive structural transformation of the material during the charge and discharge process of the battery, and thus greatly improving the electrochemical performance of the material, and improving its capacity and cycle stability. At the same time, the O3 and P2 composite phase structures offset each other's phase changes during the charge and discharge process, and the structural stability and cycle stability of the material are greatly improved under the dual effect.
[0008] To this end, the present invention provides a composite phase structure layered oxide sodium ion battery positive electrode material containing heavy elements, the chemical formula of the positive electrode material is Na a Mn x Fe y Ni z M t O2, wherein 0.8<a≤1.0, 0.25≤x≤0.35, 0.25≤y≤0.35, 0.25≤z≤0.35, 0<t≤0.05, M is one or more of the heavy elements Mo, La, Ce, W, and the sodium ion battery positive electrode material also has an O3-P2 composite phase structure.
[0009] Preferably, the chemical formula of the sodium ion battery positive electrode material is Na a Mn x Fe y Ni z M t O2, wherein the preferred range of a is 0.9≤a≤1.0, the preferred range of x, y, z is 0.30≤x, y, z≤0.35, and the preferred value of t is 0.02, 0.03 and 0.05.
[0010] Preferably, M includes a combination of heavy elements Mo and La, or a combination of W and Ce, or a combination of Mo and Ce, or a combination of W, Mo and Ce. The material also has an O3-P2 composite phase structure.
[0011] The present invention also provides a method for preparing the above-mentioned layered oxide sodium ion battery positive electrode material containing heavy metal elements, comprising the following steps:
[0012] (1) According to the chemical formula, a corresponding soluble manganese salt, a soluble iron salt and a soluble nickel salt, a precipitant and water are used to prepare a precursor through a precipitation reaction at a certain system temperature;
[0013] (2) uniformly mixing the precursor, M source compound and sodium source compound obtained in step (1) to obtain a mixture;
[0014] (3) sintering the mixture obtained in step (2) at high temperature to obtain the positive electrode material for the sodium ion battery.
[0015] Wherein, in step (1), the soluble manganese salt includes one or more of manganese sulfate, acetate, and nitrate, the soluble iron salt includes one or more of iron sulfate, acetate, and nitrate, and the soluble nickel salt includes one or more of nickel sulfate, acetate, and nitrate.
[0016] Wherein, in the step (1), the precipitant is one or more of sodium carbonate, potassium carbonate, sodium hydroxide and potassium hydroxide.
[0017] Wherein, in the step (1), the reaction system temperature is 40-70°C and the reaction time is 10-30 hours.
[0018] Wherein, in step (2), the M source compound is at least one of the oxides or sodium salts of M, for example, the M source compound includes at least one of cerium oxide, lanthanum oxide, molybdenum dioxide, tungsten oxide, sodium molybdate, and sodium tungstate.
[0019] Wherein, in step (2), the sodium source compound is at least one of sodium carbonate, sodium bicarbonate and sodium hydroxide.
[0020] Wherein, in the step (2), the molar ratio of the amount of the sodium source added in terms of sodium to the sodium ion battery positive electrode material to be prepared is >0.8-1.03:1, wherein, in the presence of high temperature loss, the sodium source is appropriately added in excess to compensate for the high temperature loss.
[0021] Wherein, in the step (3), the high temperature sintering atmosphere contains oxygen, such as air.
[0022] Wherein, in the step (3), the sintering system of the high temperature sintering is: heating to 300-500°C at a heating rate of 1-10°C / min, and keeping warm for 3-7h; then heating to 600-1000°C at a heating rate of 1-10°C / min, and keeping warm for 10-60h.
[0023] The present invention also provides a battery positive electrode material, which includes the battery positive electrode material prepared by the method for preparing the layered oxide sodium ion battery positive electrode material containing heavy metal elements.
[0024] The present invention also provides a sodium ion battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the above-mentioned layered oxide sodium ion battery positive electrode material containing heavy metal elements.
[0025] The present invention has the following beneficial technical effects:
[0026] The present invention constructs a layered oxide sodium ion battery positive electrode material containing heavy elements by regulating the elemental composition of the material, thereby achieving the following beneficial technical effects:
[0027] (1) By introducing one or more heavy elements into the layered oxide, the electronic structure of the material is changed in the crystal lattice by the heavy elements, thereby stimulating the electrochemical activity of the material, thereby improving the specific capacity of the battery. In the voltage range of 2-4.1V, the discharge specific capacity is increased by 9-15%, for example, from 131.2mAh / g to 143.4mAh / g.
[0028] (2) The stable bonding between heavy elements and oxygen greatly improves the structural stability of the material and improves the cycle performance of the material. The specific capacity retention ability after 200 cycles in the voltage range of 2-4.0V is increased by 24-30%, for example, from 61.25% to 85.30%.
[0029] (3) Starting from the perspective of strong bonding with oxygen, the present invention proposes to introduce some heavy elements into the O-type layered oxide positive electrode material, and utilizes the characteristics of these heavy elements such as Mo, La, Ce, W, etc. that have strong and stable bonding with oxygen in the crystal lattice to form, for example, a "locking effect" on the crystal structure during the charge and discharge process. At the same time, the O3-P2 phase composite structure generated by the introduction of heavy elements ensures the stability of the crystal structure of the positive electrode material, inhibits the destructive structural transformation of the material during the charge and discharge process of the battery, and thus greatly improves the electrochemical performance of the material, improves its capacity and cycle stability, and the discharge specific capacity is increased by 9-15%, and the specific capacity retention ability after 200 cycles is increased by 24-30%. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The first week charge and discharge curves of the sodium ion battery positive electrode materials prepared in Comparative Example 1 and Examples 1-4 of the present invention.
[0032] Figure 2 The charge and discharge cycle capacity retention rate curves of the sodium ion battery positive electrode materials prepared in Comparative Example 1 and Examples 1-4 of the present invention.
[0033] Figure 3 XRD curves and ratios of the sodium ion battery positive electrode materials prepared in Comparative Example 1 and Examples 1-4 of the present invention. DETAILED DESCRIPTION
[0034] The present invention will be described in further detail below in conjunction with specific embodiments. However, it should be understood that these embodiments are only for illustration and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims of the present application.
[0035] Comparative Example 1:
[0036] Comparative Example 1: Preparation of heavy element-free O3-type sodium ion battery layered oxide positive electrode material NaMn 1 / 3 Ni 1 / 3 Fe 1 / 3O2.
[0037] The preparation method comprises the following steps:
[0038] (1) dissolving manganese sulfate monohydrate, nickel sulfate hexahydrate and ferrous sulfate heptahydrate in deionized water at a stoichiometric ratio of 1:1:1 to form a 2 mol / L solution; slowly adding a precipitant solution and ammonia water into a reaction kettle under high-speed stirring, wherein the concentration of sodium hydroxide in the precipitant solution is 2 mol / L, the concentration of ammonia water is 3 mol / L, the pH value is controlled to be 10.6, the water bath temperature is controlled to be 55° C., reacting for 18 hours, filtering, washing and drying to obtain a precursor material;
[0039] (2) After sodium carbonate and the precursor material are uniformly mixed in a high-speed mixer at a molar ratio of 0.515:1, the resulting mixture is placed in a box-type muffle furnace, heated to 450°C at a heating rate of 5°C / min under air, kept at this temperature for 5 hours, and then continued to be heated to 900°C at the same heating rate, kept at this temperature for 20 hours, and cooled to room temperature to obtain the heavy element-free O3 type sodium ion battery layered oxide positive electrode material NaMn 1 / 3 Ni 1 / 3 Fe 1 / 3 O2.
[0040] like Figure 3 The figure shows the X-ray diffraction curve (XRD) of the sodium ion battery layered oxide positive electrode material obtained in Comparative Example 1, which shows a standard O3-type layered oxide structure with an R-3m space group.
[0041] Preparation of sodium ion battery: The heavy element-free O3 type sodium ion battery layered oxide positive electrode material NaMn prepared in Comparative Example 1 was 1 / 3 Ni1 / 3 Fe 1 / 3 O2, acetylene black, polyvinylidene fluoride and N-methylpyrrolidone are mixed to form a slurry, which is evenly coated on the surface of an aluminum foil to obtain a positive electrode. A metallic sodium sheet is used as a negative electrode, sodium perchlorate is used as an electrolyte salt, and propylene carbonate is used as an electrolyte solvent. The battery is assembled in a glove box to obtain a sodium ion battery.
[0042] The electrochemical performance of the sodium ion battery of Comparative Example 1 was tested using an electrochemical tester at a test temperature of 25°C. The initial charge and discharge performance of the battery was tested at a current density of 0.1C (1C = 120 mAh / g) and a voltage range of 2.0 to 4.1V. The performance results are as follows: Figure 1 As shown: the first charge and discharge specific capacities of comparative example 1 are 145.5 mAh / g and 131.2 mAh / g respectively. The cycle performance of the battery was tested at a rate of 1C, with a voltage range of 2.0 to 4.0 V. The performance results are shown in Figure 2 As shown, the capacity retention rate is 61.25% after 200 cycles.
[0043] Embodiment 1:
[0044] Example 1: A layered oxide sodium ion battery cathode material containing heavy elements Na(Mn 1 / 3 Ni 1 / 3Fe 1 / 3 ) 0.95 Mo 0.02 La 0.03 O2.
[0045] The preparation method comprises the following steps:
[0046] (1) Preparing a precursor material by the same method as step (1) in Comparative Example 1;
[0047] (2) Sodium carbonate, the above-mentioned precursor material, sodium molybdate, and lanthanum oxide were weighed at a molar ratio of 0.99:0.95:0.02:0.015 corresponding to the designed components, and then mixed evenly in a high-speed mixer. The resulting mixture was then placed in a box-type muffle furnace, heated to 450°C at a heating rate of 5°C / min under air, kept warm for 5 hours, and then continued to heat to 900°C at the same heating rate, kept warm for 20 hours, and cooled to room temperature to obtain a layered oxide sodium ion battery positive electrode material containing heavy elements Na(Mn 1 / 3Ni 1 / 3 Fe 1 / 3 ) 0.95 Mo 0.02 La 0.03 O2.
[0048] like Figure 3The X-ray diffraction curve (XRD) of the sodium ion battery layered oxide positive electrode material obtained in Example 1 shows a composite layered oxide structure, in which the O3 structure belonging to the R-3m space group and the P2 structure belonging to the P63 / mmc space group are combined.
[0049] The layered oxide sodium ion battery positive electrode material Na(Mn) containing heavy elements synthesized in Example 1 was prepared in the same manner as in Comparative Example 1. 1 / 3 Ni 1 / 3 Fe 1 / 3 ) 0.95 Mo 0.02 La 0.03 O2 was used to prepare a lithium ion battery. The electrochemical performance of the lithium ion battery of Example 1 was tested using an electrochemical tester under the same conditions as in Comparative Example 1. The initial charge and discharge performance results of Example 1 are shown in FIG. Figure 1 As shown in the figure, the first discharge capacity of Example 1 is increased from 131.2 mAh / g of Comparative Example 1 to 143.4 mAh / g, and the electrochemical activity and specific capacity of the material are greatly improved. This is due to the fact that the heavy elements change the traditional electronic structure of the material in the lattice, stimulate the electrochemical activity of the material, and thus improve the specific capacity of the battery. The cycle retention performance of Example 1 is shown in the figure. Figure 2 As shown, the capacity retention ability of Example 1 after 200 cycles is improved from 61.25% of Comparative Example 1 to 80.21%. It can be seen that the material stability and cycle stability of Example 1 are also greatly improved, which is due to the strong bonding between heavy elements and oxygen in the lattice and the O3-P2 composite phase structure brought about by the entry of heavy elements into the structure, thereby inhibiting the complex structural transformation of the material during the cycle, thereby greatly improving the cycle performance of the battery.
[0050] Embodiment 2:
[0051] Example 2: A layered oxide sodium ion battery cathode material containing heavy elements Na(Mn 1 / 3 Ni 1 / 3Fe 1 / 3 ) 0.98 W 0.01 Ce 0.01 O2.
[0052] The preparation method comprises the following steps:
[0053] (1) Preparing a precursor material by the same method as step (1) in Comparative Example 1;
[0054] (2) Sodium carbonate, the above-mentioned precursor material, sodium tungstate, and cerium oxide were weighed at a molar ratio of 1.01:0.98:0.01:0.01 corresponding to the designed components, and then mixed evenly in a high-speed mixer. The resulting mixture was then placed in a box-type muffle furnace, heated to 450°C at a heating rate of 5°C / min under air, kept warm for 5 hours, and then continued to heat to 900°C at the same heating rate, kept warm for 20 hours, and cooled to room temperature to obtain a layered oxide sodium ion battery positive electrode material containing heavy elements Na(Mn 1 / 3Ni 1 / 3 Fe 1 / 3 ) 0.98 W 0.01 Ce 0.01 O2.
[0055] like Figure 3 The X-ray diffraction curve (XRD) of the sodium ion battery layered oxide positive electrode material obtained in Example 2 shows a composite layered oxide structure, in which the O3 structure belonging to the R-3m space group and the P2 structure belonging to the P63 / mmc space group are combined.
[0056] The layered oxide sodium ion battery positive electrode material Na(Mn) containing heavy elements synthesized in Example 2 was prepared in the same manner as in Comparative Example 1. 1 / 3 Ni 1 / 3 Fe 1 / 3 ) 0.98 W 0.01 Ce 0.01 O2 was used to prepare a lithium ion battery. The electrochemical performance of the lithium ion battery of Example 2 was tested using an electrochemical tester under the same conditions as in Comparative Example 1. The initial charge and discharge performance results of Example 2 are shown in FIG. Figure 1 As shown in FIG. 1 , the first discharge capacity of Example 2 is increased to 139.6 mAh / g. The cycle retention performance of Example 2 is as follows: Figure 2 As shown, the capacity retention capacity of Example 2 after 200 cycles is improved to 85.30%. Similar to the effect of Example 1, the battery performance of Example 2 is also greatly improved compared with Comparative Example 1.
[0057] Embodiment 3:
[0058] Example 3: A layered oxide sodium ion battery cathode material containing heavy elements Na(Mn 1 / 3 Ni 1 / 3Fe 1 / 3 ) 0.97 Mo 0.02 Ce 0.01 O2.
[0059] The preparation method comprises the following steps:
[0060] (1) Preparing a precursor material by the same method as step (1) in Comparative Example 1;
[0061] (2) Sodium carbonate, the above-mentioned precursor material, sodium molybdate, and cerium oxide were weighed in a molar ratio of 0.99:0.97:0.02:0.01 corresponding to the designed components, and then mixed evenly in a high-speed mixer. The resulting mixture was then placed in a box-type muffle furnace, heated to 450°C at a heating rate of 5°C / min under air, kept warm for 5 hours, and then continued to heat to 900°C at the same heating rate, kept warm for 20 hours, and cooled to room temperature to obtain a layered oxide sodium ion battery positive electrode material containing heavy elements Na(Mn 1 / 3Ni 1 / 3 Fe 1 / 3 ) 0.97 Mo 0.02 Ce 0.01 O2.
[0062] like Figure 3 The X-ray diffraction curve (XRD) of the sodium ion battery layered oxide positive electrode material obtained in Example 3 shows a composite layered oxide structure, in which the O3 structure belonging to the R-3m space group and the P2 structure belonging to the P63 / mmc space group are combined.
[0063] The layered oxide sodium ion battery positive electrode material Na(Mn) containing heavy elements synthesized in Example 3 was prepared in the same manner as in Comparative Example 1. 1 / 3 Ni 1 / 3 Fe 1 / 3 ) 0.97 Mo 0.02 Ce 0.01 O2 was used to prepare a lithium ion battery. The electrochemical performance of the lithium ion battery of Example 3 was tested using an electrochemical tester under the same conditions as in Comparative Example 1. The initial charge and discharge performance results of Example 3 are shown in FIG. Figure 1 As shown in FIG. 1 , the first discharge capacity of Example 3 is increased to 138.8 mAh / g. The cycle retention performance of Example 3 is as follows: Figure 2 As shown, the capacity retention capacity of Example 3 after 200 cycles is improved to 69.40%. Similar to the effects of Examples 1 and 2, the battery performance of Example 3 is also greatly improved compared with Comparative Example 1.
[0064] Embodiment 4:
[0065] Example 4: Preparation of layered oxide sodium ion battery cathode material Na(Mn 1 / 3 Ni 1 / 3Fe 1 / 3 ) 0.95 Mo 0.02 Ce 0.015 La0.015 O2.
[0066] The preparation method comprises the following steps:
[0067] (1) Preparing a precursor material by the same method as step (1) in Comparative Example 1;
[0068] (2) Sodium carbonate, the above-mentioned precursor material, sodium molybdate, cerium oxide, and lanthanum oxide were weighed at a molar ratio of 0.99:0.95:0.02:0.015:0.0075 corresponding to the designed components, and mixed evenly in a high-speed mixer. The resulting mixture was then placed in a box-type muffle furnace, heated to 450°C at a heating rate of 5°C / min under air, kept warm for 5 hours, and then continued to heat to 900°C at the same heating rate, kept warm for 20 hours, and cooled to room temperature to obtain a layered oxide sodium ion battery positive electrode material NaMn containing heavy elements. 0.33 Ni 0.33 Fe 0.33 La 0.01 O2.
[0069] like Figure 3 The X-ray diffraction curve (XRD) of the sodium ion battery layered oxide positive electrode material obtained in Example 4 is shown, showing a composite layered oxide structure, in which the O3 structure belonging to the R-3m space group and the P2 structure belonging to the P63 / mmc space group are combined.
[0070] The layered oxide sodium ion battery positive electrode material Na(Mn) containing heavy elements synthesized in Example 4 was prepared in the same manner as in Comparative Example 1. 1 / 3 Ni 1 / 3 Fe 1 / 3 ) 0.95 Mo 0.02 Ce 0.015 La 0.015 O2 was used to prepare a lithium ion battery. The electrochemical performance of the lithium ion battery of Example 4 was tested using an electrochemical tester under the same conditions as in Comparative Example 1. The initial charge and discharge performance results of Example 4 are shown in FIG. Figure 1 As shown in FIG. 1 , the first discharge capacity of Example 4 is increased to 141.3 mAh / g. The cycle retention performance of Example 4 is as follows Figure 2 As shown, the capacity retention capacity of Example 4 after 200 cycles is improved to 79.63%. Similar to the effects of Examples 1-3, the battery performance of Example 4 is also greatly improved compared with Comparative Example 1.
[0071] From the above, it can be seen that compared with Comparative Example 1, which is a layered oxide positive electrode material containing no heavy elements and no composite phase structure, the specific capacity and cycle stability of the sodium ion batteries prepared by the layered oxide sodium ion battery positive electrode materials containing heavy elements and O3-P2 composite phase structure in Examples 1-4 are greatly improved.
Claims
1. A composite phase structure layered oxide sodium ion battery positive electrode material containing heavy elements, the chemical formula of the positive electrode material is Na a Mn x Fe y Ni z M t O2, wherein 0.8<a≤1.0, 0.25≤x≤0.35, 0.25≤y≤0.35, 0.25≤z≤0.35, 0<t≤0.05, M is one or more of the heavy elements Mo, La, Ce, W, and the sodium ion battery positive electrode material also has an O3-P2 composite phase structure.
2. The composite phase structure layered oxide sodium ion battery positive electrode material containing heavy elements as claimed in claim 1, wherein a is 0.9≤a≤1.0; x, y, and z are all in the range of 0.30-0.
35.
3. The composite phase structure layered oxide sodium ion battery positive electrode material containing heavy elements according to claim 1, wherein: M includes a combination of heavy elements Mo and La, or a combination of W and Ce, or a combination of Mo and Ce, or a combination of W, Mo and Ce.
4. The method for preparing a layered oxide sodium ion battery positive electrode material containing heavy metal elements according to any one of claims 1 to 3, comprising the following steps: (1) According to the chemical formula, a corresponding soluble manganese salt, a soluble iron salt and a soluble nickel salt, a precipitant and water are used to prepare a precursor through a precipitation reaction at a certain system temperature; (2) uniformly mixing the precursor, M source compound and sodium source compound obtained in step (1) to obtain a mixture; (3) sintering the mixture obtained in step (2) at high temperature to obtain the positive electrode material for the sodium ion battery.
5. The method for preparing a layered oxide sodium ion battery positive electrode material containing heavy metal elements as claimed in claim 4, wherein: In the step (1), the precipitant is one or more of sodium carbonate, potassium carbonate, sodium hydroxide and potassium hydroxide.
6. The method for preparing a layered oxide sodium ion battery positive electrode material containing heavy metal elements according to claim 4, wherein: In the step (2), the M source compound is at least one of an oxide or a sodium salt of M.
7. The method for preparing a layered oxide sodium ion battery positive electrode material containing heavy metal elements according to claim 4, wherein: In the step (2), the molar ratio of the amount of the sodium source added in terms of sodium to the sodium ion battery positive electrode material to be prepared is >0.8-1.03:
1.
8. The method for preparing a layered oxide sodium ion battery positive electrode material containing heavy metal elements as claimed in claim 4, wherein: In the step (3), the high temperature sintering atmosphere contains oxygen.
9. The method for preparing a layered oxide sodium ion battery positive electrode material containing heavy metal elements as claimed in claim 4, wherein: In the step (3), the sintering system of the high temperature sintering is: first heating to 300-500°C and keeping the temperature for a certain time; then heating to 600-1000°C and keeping the temperature for a certain time.
10. A sodium ion battery comprising a positive electrode, a negative electrode and an electrolyte, wherein: The positive electrode comprises the layered oxide sodium ion battery positive electrode material containing heavy metal elements as described in any one of claims 1 to 3.
Citation Information
Patent Citations
Hybrid-phase structure layered oxide material and preparation method and application thereof
CN109585795A
O3-P2 composite phase sodium ion positive electrode material as well as preparation method and application thereof
CN115148984A
Sodium-ion battery positive electrode material as well as preparation method and application thereof
CN115295787A
High-entropy doped layered oxide, preparation method thereof, positive electrode material and sodium ion battery
CN116425212A
Sodium-ion battery positive electrode material with gradient structure as well as preparation method and application of sodium-ion battery positive electrode material
CN118676349A